IMPLEMENTATION OF BIDIRECTIONAL VOICE COMMUNICATION BETWEEN NORMAL AND DEAF & DUMB PERSON - Saraswathi, V.; Sushmitha, S.; Saranya, C. (IJRDO -Journal of Computer Science Engineering, 2016)
In the existing system there is no handrecognition system to indicate the actions. In the proposedsystem, Android Application is employed to grab Imagesthrough Camera. The main idea of the paper is to understandthe communication of the deaf and dumb people. Deaf andDumb people will show their Hand Gesture in front of Cameraand it sends to the Server. Server processes the Hand Gestureand corresponding Voice alert is played in the Normal Personside (Android). In the modification, Normal Person will speakthrough the Android Application, which recognizes the Voiceinput and it converts into Hand Gesture image to the Deaf &Dumb Person. We can also transfer the Hand Gesture input bydeaf & dumb person to multiple Android normal People. Wecan Establish Two way Communication between Deaf &Dumb child with normal Child.